2017
DOI: 10.1292/jvms.17-0450
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal implantation of Okayama University-type retinal prosthesis (OUReP<sup>TM</sup>) in canine eyes by vitrectomy

Abstract: Okayama University-type retinal prosthesis (OURePTM) is a photoelectric dye-coupled polyethylene film which generates electric potential in response to light and stimulates nearby neurons. This study aims to test surgical feasibility of subretinal implantation and functional durability of dye-coupled films in the subretinal space. The dye-coupled films were implanted subretinally by 25-gauge vitrectomy in the right eye of 11 normal beagle dogs: 2 dogs served for film removal after 5-month film implantation, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In the present study, electric potential changes generated in response to light on the dye-coupled lm surface were successfully measured by the Kelvin probe. The Kelvin probe system has been renovated with humidity control of the atmosphere to measure surface electric potential of dye-coupled lms reproducibly at a steady level [17,18]. The slope-like trivial drift of baseline of electric potential in repeat episodes of lighton-and-off would be attributed to the accumulation of static electricity on the dye-coupled lm surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, electric potential changes generated in response to light on the dye-coupled lm surface were successfully measured by the Kelvin probe. The Kelvin probe system has been renovated with humidity control of the atmosphere to measure surface electric potential of dye-coupled lms reproducibly at a steady level [17,18]. The slope-like trivial drift of baseline of electric potential in repeat episodes of lighton-and-off would be attributed to the accumulation of static electricity on the dye-coupled lm surface.…”
Section: Discussionmentioning
confidence: 99%
“…2.2 Light-evoked surface electric potential measurement Light-evoked electric potential of the lm surface was measured using a scanning Kelvin probe system (SKP5050 with a light source, Surface Photovoltage Spectroscopy SPS040, KP Technology, Highlands and Islands, UK, Fig. 2) in the surface photovoltage mode [17,18]. The dye-coupled lm was xed on a sample device under dry condition in a humidity controlled box with nitrogen gas ow (Fig.…”
Section: Preparation Of Photoelectric Dye-coupled Poly-mentioning
confidence: 99%
“…The goals of this study are two folds: the first to test surgical feasibility of subretinal film implantation by vitrectomy in rabbits, and the second to test functional durability of the implanted films. In the previous study [ 17 ], beagle dogs were used for dye-coupled film implantation. The canine study demonstrated technical feasibility of film implantation and 5-month functional durability of the implanted films.…”
Section: Discussionmentioning
confidence: 99%
“…Sophisticated techniques are required to implant surgically the multielectrode arrays. In contrast, the dye-coupled film is a soft and thin sheet which would be rolled up and inserted in subretinal space by routine vitrectomy [ 16 , 17 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation